A Study of Obesity and Sleep Disordered Breathing - Dr. Priyanka Joshi; Dr. Rekha Mehani (International Journal of Medical Research and Review, 2021)
Introduction: Obstructive sleep apnea (OSA) is associated with increased cardiovascular morbidity and mortality and various Cardiovascular risk factors. Obesity is strongly linked with respiratory symptoms and diseases like dyspnea on exertion, obstructive sleep apnea syndrome (OSAS). This study has been undertaken to analyze the severity of hypertension in obese patients, sleep-disordered breathing (SDB) in obese patients, to analyze whether SDB is a risk factor for hypertension in obese individuals and to correlate how many obese hypertensives have correctable SDB. Methods: A total of 200 obese patients were randomly selected from the outpatient department. Berlin’s questionnaire and the Epworth sleepiness scale score (ESSS) were used to assess sleep-disordered breathing (SDB). Asian classification of obesity suggested by the World Health Organization was used for the assessment of BMI. All statistical analysis was carried out using the SPSS version20, and Appropriate Statistical tools were applied wherever required, like a test of proportion, Chi-square test etc. Results: Out of 200 subjects, 116 were male, and 84 were female. The majority of the study population (70.0%) had suffered from obstructive sleep apnea, while the rest (30.0%) had mixed sleep apnea. The mean spread of age for total selected subjects (N=200) was 45.64±12.75 years. The body mass index (BMI) between 40 and 50 kg/m2 in 49.0% obese patient. Systemic hypertension prevailed more in male (81.0%) obese subjects than female (77.4%) obese subjects. The most significant risk factor for predicting hypertension was moderate type sleep apnea (p<0.005) followed by the age of the (p<0.007) obese patients that were confirmed strongly significant on the statistical ground. Conclusion: Obesity has a very high and proportionate correlation between sleeping disordered breathing. Obstructive sleep apnea is the predominant sleep-disordered breathing in our study population. Sleep-disordered breathing is very much correctable in the obese hypertensive population by weight reduction and risk factor control.